Sex Differences in Cardiovascular Risk Factors and Renal Function among Young Adults after Intrauterine Growth Restriction - Lorka Tarnovski; Ivana Vuković Brinar; Majda Vrkić Kirhmajer; Tajana Željković Vrkić; Mario Laganović (Acta Clinica Croatica, 2021)
Introduction: Intrauterine growth restriction (IUGR) is linked to a higher incidence of cardiovascular and renal diseases. Methods: A total of 91 healthy individuals were included, 40 women and 51 men, born below the 10th percentile of birth weight for gestational age. Anthropometric parameters, arterial pressure (AP), blood glucose, estimated glomerular filtration rate (eGFR), albumin/creatinine ratio, lipid profile, uric acid, renal volume by ultrasound, pulse wave velocity, central arterial pressure (cAP), and augmentation index (Aix) were measured. Results: Men have higher body mass index (BMI), waist circumference, ambulatory and continuous AP, lower eGFR, pulse, higher uric acid and LDL cholesterol, lower HDL cholesterol, higher cAP and Aix, higher corrected renal volume, and birth weight than females. Overweight men had hypertension, lower eGFR, and dyslipidemia more often. Systolic pressure correlated positively with BMI in men. In women, systolic pressure correlated positively with heart rate and negatively with gestational age. BMI affected the systolic pressure in men and eGFR in women. Conclusion: Results indicate the more unfavourable effect of IUGR on men. Higher AP, vascular dysfunction, poorer renal function, and dyslipidemia predispose men to earlier chronic disease development.